Endothelial cell-derived extracellular vesicles impair the angiogenic response of coronary artery endothelial cells - Carter, Nigeste; Mathiesen, Allison H.; Miller, Noel; Brown, Michael; Colunga Biancatelli, Ruben M. L.; Catravas, John D.; Dobrian, Anca D. (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular disease (CVD) is the most prominent cause of death of adults in the United States with coronary artery disease being the most common type of CVD. Following a myocardial event, the coronary endothelium plays an important role in the recovery of the ischemic myocardium. Specifically, endothelial cells (EC) must be able to elicit a robust angiogenic response necessary for tissue revascularization and repair. However, local or distant cues may prevent effective revascularization. Extracellular vesicles (EV) are produced by all cells and endothelium is a rich source of EVs that have access to the main circulation thereby potentially impacting local and distant tissue function. Systemic inflammation associated with conditions such as obesity as well as the acute inflammatory response elicited by a cardiac event can significantly increase the EV release by endothelium and alter their miRNA, protein or lipid cargo. Our laboratory has previously shown that EVs released by adipose tissue endothelial cells exposed to chronic inflammation have angiostatic effects on naïve adipose tissue EC in vitro. Whether the observed effect is specific to EVs from adipose tissue endothelium or is a more general feature of the endothelial EVs exposed to pro-inflammatory cues is currently unclear. The objective of this study was to investigate the angiostatic effects of EVs produced by EC from the coronary artery and adipose microvasculature exposed to pro-inflammatory cytokines (PIC) on naïve coronary artery EC. We have found that EVs from both EC sources have angiostatic effects on the coronary endothelium. EVs produced by cells in a pro-inflammatory environment reduced proliferation and barrier function of EC without impacting cellular senescence. Some of these functional effects could be attributed to the miRNA cargo of EVs. Several miRNAs such as miR-451, let-7, or miR-23a impact on multiple pathways responsible for proliferation, cellular permeability and angiogenesis. Collectively, our data suggests that EVs may compete with pro-angiogenic cues in the ischemic myocardium therefore slowing down the repair response. Acute treatments with inhibitors that prevent endogenous EV release immediately after an ischemic event may contribute to better efficacy of therapeutic approaches using functionalized exogenous EVs or other pro-angiogenic approaches.